Perananan Panti Asuhan dalam Menunjang Pendidikan Anak Asuh (Studi Kasus LKSA Yayasan Darul Hikmah) - Purnia, Poppy; Syawaluddin, Syawaluddin (Al-DYAS, 2023)
This article was created aiming to find out how the activities of foster children at the Darul hikmah orphanage, how the parenting style is applied by the orphanage, and finally to find out what efforts are made by the orphanage in supporting the education of the orphanage. The results of the research on the role of the Darul Hikmah orphanage in supporting children’s education formally, namely providing education services for elementary, junior high, and high school. And children are free to choose the school they want. While informally, namely religious education (spiritual), learning to sew and computers. So it can be concluded regarding the role of the Darul Hikmah orphanage in supporting the education of foster children, in general the administrators of the orphanage do it according to the rights that children get in their own families, both formal and informal education.